Coupling of rare earth moment and charge density wave ordering in a single crystal Er2Ir3Si5. (18th March 2015) - Lalngilneia, P C; Thamizhavel, A; Ramakrishnan, S; Pal, D
Abstract: Charge Density Wave (CDW) transitions are well known phenomena in a large variety of quasi-low dimensional conductors. Their appearance is basically due to the low dimensionality which facilitates Fermi surface nesting. We have shown that both Lu2 Ir3 Si5 and Er2 Ir3 Si5 are two new CDW compounds whose structure is 3-D in nature [1, 2]. The nesting of Fermi surfaces leads to the appearance of a periodic lattice distortion with an accompanying energy gap opening at the Fermi level [3]. In this work, we report the bulk characterization of a high quality single crystal of Czochkralski pulled Er2 Ir3 Si5 using transport and magnetization measurements. These studies establish multiple charge density wave transitions in this crystal with coupling of the Er moments to the CDW ordering as evidenced by the magnetization measurement. Such a coupling is rather unusual in rare earth compounds that display CDW transition. Possibility of modulated magnetism of Er moments due to CDW will be discussed.